ANALISIS PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS PELANGGAN PT GARUDA INDONESIA (PERSERO) TBK BRANCH OFFICE SEMARANG - Alifatul Amiroh; Putut Haribowo (Politeknik Negeri Semarang, 2017)
The purpose of this research is to find out the influence of customer relationship managementwhose variable consist of continuity marketing, one to one marketing, and partnering programon the customer loyalty at PT Garuda Indonesia (persero) Tbk branch office Semarang. Dataobtained from literature search and spreading of the questionnaire to 100 respondents bypurposive sampling techniques. Meanwhile, the analysis techniques uses validity test, reliabilitytest, normality test, multikolinearity test, heteroskedasticity test, linearity test, multiple linierregression analysis, T test, F test, and coefficient of determination. Based on the calculationsusing SPSS version 24, the result of the research showed that the regression equation Y = 0,117+ 0,313 + 0,494 + 0,189 + e. It means that continuity marketing, one to one marketing,and partnering program have significant and positive influence on the customer loyalty. Themost influence variable is one to one marketing with the highest coefficient regression of 0,494.The coefficient of determination test is 0,490. It means that the customer loyalty of 49,0% isinfluenced by continuity marketing, one to one marketing, and partnering program. While therest of 51,0% is influenced by other factors